A new species of arboreal pitviper from the Atlantic versant of northern Central America - Campbell, Jonathan A (2000)
A new species of green, prehensile-tailed pitviper of the genus Bothriechis is described from the Atlantic slopes of eastern Guatemala and western Honduras. This species appears to be most closely related to B. bicolor of the Pacific versant of Chiapas (Mexico) and Guatemala. Several other species of Bothriechis occur on the Atlantic versant of northern Central America, including two montane species, B. aurifer and B. marchi but, with one possible exception, these are not known to be sympatric with the new species and occur in different mountain ranges. The widespread B. schlegelii occurs up to at least 900 m on the Sierra de Caral, where the lowest elevation recorded for the new species is 885 m.